PERTANGGUNGJAWABAN PIDANA ATAS PENYALAHGUNAAN PEMBAYARAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) OLEH PEJABAT PEMBUAT AKTA TANAH (PPAT) - Intifada Atin Nisya’ (Jurnal HUKUM BISNIS, 2019)
This journal is entitled as Criminal Liability for Misappropriation Payments for the Acquisition of Land and Building Rights (BPHTB) by Official Certifier of Title Deeds (PPAT). Normative juridical legal research was applied in this study. The approach used in this problem is the legal approach (statute approach), case approach (case approach), and conceptual approach (conceptual approach). The background study of this thesis is about the problem for the notary as the Official Certifier of Title Deeds / Land Deed Official (PPAT) who is involved in a criminal act. There are several cases of tax evasion and also fictitious tax invoices. One of the cases in this case is the PPAT in Semarang, which ended is subject to criminal acts of Corruption. It was proved by the tax payment money when he should have paid the tax but not paid and she did some data manipulation to enrich himself. In order to establish an action as a violation against the law, the loss of state finances or just against the law has an item belonging to another person in his power, where the goods are not from the proceeds of crime. Based on this background, there are two main issues, namely How does the Ratio Decide in court decisions related to cases of misuse of BPHTB payments made by PPAT and What is the validity of the sale and purchase deed if BPHTB tax invoice and PPh (final) falsified?